Chrystal Macmillan, Scottish campaigner for women's equality through law reform. Issue 4 (6th June 2020) - Kay, Helen; Pipes, Rose
ABSTRACT: This article will explore the work of Chrystal Macmillan, who used her knowledge of the law to further the cause of women's equality through her committee work with several voluntary organisations, and her presentations to the British Government, the League of Nations, and the International Labour Office. Using archival material, both from committee minutes and family anecdotes, we will show the substantial amount of voluntary work undertaken by Chrystal Macmillan both before and after she became a practising lawyer in 1924. The article will also try to capture something of the woman's character through the comments of her friends and colleagues.